Organosilane composite plastic scintillator with excellent neutron gamma discrimination capability and preparation method thereof
By using organosilane DDS and organic plastic polymer VT as a blending matrix, and adding fluorescent dyes and other additives, an organosilane composite plastic scintillator with excellent neutron/gamma identification and good radiation resistance is prepared, which solves the problem of insufficient scintillator performance in the prior art, and achieves efficient neutron/gamma identification and good mechanical properties.
Patent Information
- Application Number
- CN202411901413.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-14
AI Technical Summary
Existing plastic scintillators have shortcomings in neutron/gamma identification, radiation resistance, mechanical strength, optical transparency and cost, and are difficult to meet the needs of a variety of physical applications.
Organosilane composite plastic scintillator with excellent neutron/gamma screening ability was prepared by combining the main fluorescent dye 2,5-diphenyloxazole (PPO), the secondary fluorescent dye 7-diethylamino-4-methylcoumarin (MDAC), the crosslinker divinylbenzene (DVB), and the initiator azobisisobutyronitrile (AIBN).
It achieves high transparency, excellent neutron/gamma screening performance, good radiation resistance and mechanical processing performance, while reducing production costs.
Smart Images

Figure CN119613884A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an organic silane composite plastic scintillator with excellent neutron / gamma discrimination capability and a preparation method thereof, belonging to the field of nuclear technology and application. Background Art
[0002] Scintillator materials play an important role in the fields of nuclear energy, homeland security, medical imaging and high-energy physics. Plastic scintillators are widely used in passive nuclear material detection, nuclear physics experiments, spallation neutron sources, nuclear fission / fusion reactors, and nuclear astronomical processes that produce mixed pulses of neutrons and gamma rays due to their low cost, fast attenuation, and easy preparation of large sizes. Neutron detection requires neutron / gamma (n / γ) discrimination. n / γ discrimination uses the differences in the speed of the incident particles, the mechanism of interaction between the particles and the detection medium material, and the reaction products to achieve the distinction between neutrons and gamma rays. We usually use pulse shape discrimination (PSD) to evaluate the n / γ discrimination ability of scintillators. Neutrons and gamma rays excite fluorescent molecules in scintillators through energy loss, producing two pulse components, fast and slow. Since the proportion of the slow component of neutrons is greater than that of gamma rays, the PSD method uses this difference to distinguish neutrons from gamma rays in the pulse amplitude integral spectrum. The indicator used to measure the n / γ discrimination capability of the detector is the optimization factor (FoM), which is defined as the ratio of the peak spacing of the neutron and gamma-ray signal pulse amplitudes to the sum of the half-height full widths of the two peaks. However, the current commercial plastic scintillators have certain deficiencies in n / γ resolution, radiation resistance, mechanical strength, optical transparency and cost, and are difficult to meet the needs of a variety of physical applications. Therefore, it is of great significance to develop a new type of scintillator detector with low production cost, high optical transparency, strong radiation resistance and good n / γ discrimination capability.
[0003] Existing plastic scintillators have good neutron / gamma discrimination capabilities, but after absorbing high doses of radiation, the scintillator itself will turn yellow and the performance of the scintillator will drop sharply. Existing polysiloxane scintillators have good radiation resistance, but weak neutron / gamma discrimination capabilities, lack of mechanical processing capabilities, and poor practical application capabilities. P.Μ.Zhmurin et al. studied polysiloxane groups with high phenyl chromophore content and obtained polysiloxane scintillators with radiation hardness one order of magnitude higher than conventional plastic scintillators. With reference to this study, we want to combine siloxane and plastic scintillators to prepare a new scintillator that has the performance of both plastic scintillators and polysiloxane scintillators, while having excellent neutron / gamma discrimination and light yield capabilities, improving the scintillator's radiation resistance and making the scintillator machinable. We try to find a new organosilane, and by compounding it with organic plastic polymer PVT, we develop a new organosilane composite plastic scintillator that has high transparency and n / γ capabilities, while improving the scintillator's mechanical processing capabilities and radiation resistance. (Zhmurin, P.Μ.et al. Radiation hardness of polysiloxane-based scintillators. Problems of Atomic Science and Technology, (2022) 38-42) Summary of the invention
[0004] In view of the shortcomings of existing plastic scintillators in n / γ discrimination, radiation resistance and other performances, the purpose of the present invention is to provide an organosilane composite plastic scintillator and a preparation method thereof, which uses organosilane and plastic as a blending matrix to form a composite structure of organosilane and plastic blending polymerization, and has excellent n / γ discrimination performance and light yield, high light transmittance, high elasticity.
[0005] In order to achieve the above technical objectives, the present invention adopts the following technical solutions:
[0006] The invention discloses an organosilane composite plastic scintillator with excellent neutron / gamma discrimination capability and a preparation method thereof. The organosilane composite plastic scintillator is composed of organosilane and organic plastic polymer as a matrix, a primary fluorescent dye, a secondary fluorescent dye, a crosslinking agent and an initiator. The organosilane is diphenyldimethoxysilane (DDS), the organic plastic polymer is vinyltoluene (VT), the primary fluorescent dye is 2,5-diphenyloxazole (PPO), the secondary fluorescent dye is 7-diethylamino-4-methylcoumarin (MDAC), the crosslinking agent is divinylbenzene (DVB), and the initiator is azobisisobutyronitrile (AIBN).
[0007] The organosilane composite plastic scintillator of the present invention uses DDS and VT as a blending matrix, which are evenly mixed and then added with an organic dye to prepare a scintillator. The inventor unexpectedly discovered that the scintillator prepared by using DDS and VT as a mixed matrix can well distinguish neutrons from gamma rays in a high-dose mixed radiation field, and the overall transparency is very high. The scintillator is an elastomer with good resilience and can be polished and processed into a specific shape according to requirements. DDS contains a large number of silicon-oxygen bonds, has a high bond energy, and has better radiation resistance. At the same time, the cost of DDS is low, and the cost of organic polymers can be reduced by adding DDS.
[0008] In addition, organic chemical PPO containing a large number of electronic conjugated bond structures has a strong spin-orbit interaction force, which can realize the energy transfer of excitation energy from the matrix to the electronic energy level in its molecule, and the fluorescence emission peak is at 365nm, so the present invention uses PPO as the main fluorescent dye. Doping with high concentrations of dyes (main dyes) will lead to a certain self-absorption effect and weaken the fluorescence emission intensity, but the added high concentration is beneficial to the neutron / gamma discrimination performance of its scintillator, so we add a small amount of secondary fluorescent dye MDAC to absorb the fluorescence emitted by the main fluorescent dye, and emit a fluorescence spectrum with a longer wavelength of fluorescence, which can improve the neutron / gamma discrimination ability while weakening the self-absorption effect.
[0009] Through a large number of experiments, the present invention uses DDS and VT as a blend matrix, PPO as a primary fluorescent dye, and MDAC as a secondary fluorescent dye. Under the synergistic effect of the above materials, the prepared organic silane composite plastic scintillator has a strong discrimination ability for neutrons / gamma in a mixed pulse radiation field, which is stronger than general commercial plastic scintillators, and also has good optical properties, radiation resistance and resilience.
[0010] In a preferred embodiment, the organosilane is DDS, and its mass fraction in the blend matrix is 20-40wt%.
[0011] The inventors found that when the organosilane is selected from DDS, the organosilane composite plastic scintillator finally prepared has very good neutron / gamma discrimination ability, low cost and optimal molding rate during the preparation process, and has very good resilience performance.
[0012] In a preferred embodiment, the organic plastic polymer is VT, and its mass fraction in the matrix is 80-60wt%.
[0013] The inventors found that when the organic plastic polymer is selected from VT, the neutron / gamma discrimination capability of the finally prepared organic silane composite plastic scintillator is the best and the molding rate in the preparation process is the best.
[0014] In a preferred embodiment, the mass fraction of the main fluorescent dye in the organosilane composite plastic scintillator is 30wt%.
[0015] In a preferred embodiment, the mass fraction of the secondary fluorescent dye MDAC in the organosilane composite plastic scintillator is 0.2 wt %.
[0016] In a preferred embodiment, the mass fraction of the crosslinking agent DVB in the organosilane composite plastic scintillator is 2 wt %.
[0017] In a preferred embodiment, the mass fraction of the initiator AIBN in the organosilane composite plastic scintillator is 0.05wt%
[0018] In the present invention, the combination of primary fluorescent dye and secondary fluorescent dye is PPO+MDAC, and the added mass fraction is fixed. This is because the wavelength matching degree of PPO and MDAC is very good, and the energy captured by the matrix can be well transferred to the primary fluorescent dye molecule, and then transferred to the secondary fluorescent dye molecule, and finally the emission is received by the photomultiplier tube, which can effectively reduce the self-absorption effect of the scintillator itself, and will not affect the optical transparency of the scintillator.
[0019] In the present invention, the ratio of the organosilane DDS to the organic plastic polymer VT needs to be maintained within a certain ratio. When the added content of DDS is too high, it will cause polymerization failure or large-scale cracking and cannot be used; when the added amount is too low, its performance cannot be improved. At the same time, the addition amount of the main fluorescent dye PPO, the secondary fluorescent dye MDAC, etc. also needs to be precisely controlled; excessive addition of fluorescent dyes will cause the dye molecules to precipitate and settle at the bottom of the scintillator or suspend in the scintillator, making the transparency, mechanical strength and stability of the plastic scintillator worse. Adding too little fluorescent dye will make the scintillator fluorescence intensity insufficient, the quality factor (FoM value) of n / γ pulse shape discrimination low, and it is difficult to discriminate neutrons and gamma rays.
[0020] In the present invention, the content of the added crosslinking agent should not be too high and should be maintained within a reasonable range, because adding too high a concentration will also cause a large number of cracks in the composite scintillator and the surface will continue to have organic dyes. When the added concentration is too low, the polymerization process of the scintillator will be prolonged and the scintillator will turn yellow.
[0021] The present invention provides a preparation method of an organosilane composite plastic scintillator with excellent neutron / gamma discrimination ability and a preparation method thereof, comprising the following steps: preparing DDS, VT and divinylbenzene (DVB), mixing and stirring, and ultrasonicating to make them uniformly mixed, to obtain a mixed solution A; preparing PPO, MDAC, and azobisisobutylnitrile (AIBN) to obtain a mixed powder B; adding the mixed powder B to the mixed solution A, dissolving through ultrasonic dispersion to obtain a mixed precursor solution C; pouring the mixed precursor solution C into a customized glass mold, and ultrasonically dispersing it again. Then, the precursor solution C is purified, and the purification treatment is vacuuming and then filling with inert gas, and the purification treatment is repeated ≥3 times. Then, a thermal polymerization reaction is carried out in a vacuum environment, and after the reaction is completed, a stress relief annealing treatment is carried out to finally obtain an organosilane composite plastic scintillator.
[0022] In the present invention, the organosilane composite plastic scintillator is first purified before the polymerization reaction. The inventors have found that this operation can optimize the performance of the organosilane composite plastic scintillator obtained by the final reaction.
[0023] In a preferred embodiment, the stress relief annealing treatment is performed for 48 hours, and the temperature during the stress relief annealing treatment is 60°C.
[0024] The inventors found that the temperature and time control of stress relief annealing are related to the stability of the scintillator, and stress relief annealing can effectively eliminate internal stress. However, when the stress relief annealing temperature is too high, it will cause cracks on the surface of the scintillator, and when it is too low, it will greatly prolong the aging time, increase time and labor costs. The stress relief annealing time is generally about 48 hours, which can effectively shorten the time and eliminate the internal stress of the scintillator to the greatest extent.
[0025] In a preferred embodiment, the mass ratio of DDS to VT is 20-40:80-60.
[0026] The inventors found that when the mass ratio of DDS to VT is controlled within the range of 20-40:80-60, an organosilane composite plastic scintillator with transparent texture, good resilience and excellent neutron / gamma discrimination performance can be obtained. In the present invention, the mass ratio of DDS to VT is set to 20-40:80-60, which represents the composition ratio of DDS and VT in the scintillator.
[0027] In a preferred embodiment, in the organosilane composite plastic scintillator, the mass fraction of the primary fluorescent dye PPO is 30 wt %, and the mass fraction of the secondary fluorescent dye MDAC is 0.2 wt %.
[0028] In a preferred embodiment, in the organosilane composite plastic scintillator, the mass fraction of azobisisobutyronitrile (AIBN) is 0.05 wt %.
[0029] In a preferred embodiment, in the organosilane composite plastic scintillator, the mass fraction of divinylbenzene (DVB) is 2 wt %.
[0030] In a preferred embodiment, the inert gas is nitrogen.
[0031] In a preferred embodiment, the purification process is repeated three times.
[0032] In a preferred embodiment, the polymerization reaction process is as follows: first, keep the temperature at 50-55°C for 12-24 hours; then heat to 70-75°C at a rate of 5-8°C / h, keep for 8-16 hours; then heat to 100-110°C at a rate of 5-8°C / h, keep for 8-16 hours; then cool to 70-75°C at a rate of 3-5°C / h, keep for 12-24 hours; then cool to 45-50°C at a rate of 3-5°C / h, keep for 12-24 hours, cool to room temperature after keeping; then place it in an oven and heat to 60°C for stress relief annealing for 48 hours, and then slowly cool to room temperature. If the stress relief annealing process is not performed, the scintillator will be less stable in an air environment due to the influence of internal stress, and cracks will easily occur, resulting in poor performance or even unusable performance.
[0033] The polymerization process of the present invention can ensure that the organic silane and the organic plastic polymer can fully undergo polymerization reaction by controlling the temperature increase step, and the entire polymerization reaction process can be fully and smoothly carried out. In addition, a gradient temperature increase and decrease method is adopted during the temperature increase and decrease period to avoid cracking and microcracks of the formed scintillator due to the rapid temperature change process, thereby ensuring that the scintillator performance is in the best state.
[0034] In practical applications, the surface of the organosilane composite plastic scintillator of the present invention needs to be polished and ground first so that it can perfectly fit the photoelectric detector and improve the detection efficiency.
[0035] The present invention discloses an organosilane composite plastic scintillator with excellent neutron / gamma discrimination capability and an application of a preparation method thereof. The organosilane composite plastic scintillator is applied to neutron detection in a pulse radiation field mixed with neutrons and gamma rays. The detection performance of the detector is higher than that of a conventional plastic scintillator.
[0036] Principles and advantages:
[0037] In the present invention, DDS is added to the formula of a conventional plastic scintillator, polymerization can occur and a composite scintillator can be successfully prepared. DDS is an organic silane containing a benzene ring, which can be polymerized into chains under the addition of an initiator. The bond energy of the silicon-oxygen bond of DDS is higher than that of the carbon-carbon bond, which can effectively improve the radiation resistance of the scintillator, and DDS has better solubility for dyes. By adjusting the ratio of organic plastic polymers and DDS, the solubility of the added organic luminescent dyes PPO, MDAC, etc. in the scintillator can be made so that the prepared scintillator has better optical properties and light yield, and the detection efficiency of neutrons / gamma will also be improved. In addition, the cost of DDS is lower than that of conventional plastic organic polymers, which can reduce the cost expenditure in production and is organic for future commercial production.
[0038] The energy transfer process of the present invention is described as follows: vinyltoluene and diphenyldimethoxysilane are used as energy donors (mainly VT and DDS), PPO is used as the first energy acceptor and singlet / triplet scavenger, and MDAC is used as the second energy acceptor.
[0039] The advantages and effects of the present invention are: mainly under the joint action of vinyltoluene (VT) molecules and diphenyldimethoxysilane (DDS), different incident particles (neutrons, gamma rays, etc.) lose energy due to elastic scattering and photoelectric effect; compared with gamma rays, neutrons produce a higher triplet density in the scintillator matrix, so that the slow component accounts for a higher proportion in the fluorescent component, which is the key to distinguishing neutrons from gamma rays. The scintillator polymerized by DDS doping can effectively improve the radiation resistance because of its silicon-oxygen bond, and at the same time, its good solubility can effectively improve its dye solubility, ensuring that the scintillator has good optical transparency and neutron / gamma discrimination ability, thereby further improving the performance of the scintillator. The organic silane composite plastic scintillator polymerized by DDS doping has excellent optical properties and low preparation cost, as well as the ability to detect neutrons and radiation resistance in mixed radiation fields, and its commercial prospects are broad. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 These are sample images of Examples 1-5 of the present invention taken under visible light and ultraviolet light.
[0041] Figure 2 It is the two-dimensional PSD spectrum of Examples 1-5 of the present invention and the commercial EJ276 sample.
[0042] Figure 3 For the embodiments 1-5 of the present invention and the commercial EJ200 137 Cs pulse height spectrum.
[0043] Figure 4This is the excitation-emission fluorescence spectrum of Example 3 of the present invention.
[0044] Figure 5 It is the UV-visible light transmittance spectrum of Examples 1-5 of the present invention.
[0045] Figure 6 It is the thermogravimetric curve diagram of Examples 1-5 and Example 6 of the present invention.
[0046] Figure 7 This is a microscopic image of Example 3 of the present invention under a metallographic microscope. DETAILED DESCRIPTION
[0047] The preparation of the organosilane composite plastic scintillator of the present invention is further described below through specific examples.
[0048] Example 1
[0049] (1) The mass ratio of VT to DDS in the matrix was set to 80:20. 2.8 g VT and 0.7 g DDS were weighed according to the mass percentage, added into a test tube and ultrasonically mixed evenly. Then 0.07 g divinylbenzene (DVB) was added thereto and mixed evenly to prepare a mixed solution A. Then, according to the mass percentage, 1.05 g of the primary fluorescent dye 2,5-diphenyloxazole (PPO), 0.007 g of the secondary fluorescent dye 7-diethylamino-4-methylcoumarin (MDAC), and 0.00175 g of the initiator azobisisobutyronitrile (AIBN) were added to another test tube to obtain a mixed powder B; the mixed solution A was transferred to the test tube of the mixed powder B through a disposable dropper, mixed and shaken, and then ultrasonicated for 5 minutes. The next step can be performed after all the powder particles are completely dissolved, and a precursor solution C is obtained; at this time, the proportion of DVB in the precursor solution C is 2wt%, of which the proportion of PPO is 30wt%, the proportion of MDAC is 0.2wt%, and the proportion of AIBN is 0.05wt%.
[0050] (2) Purifying the precursor solution C by evacuating the solution and then filling it with an inert gas (nitrogen). The solution is evacuated for 3 minutes through a double-row pipe device, and then nitrogen is introduced for 2 minutes. The purification process is repeated 3 times. The test tube is sealed with a flamethrower and then placed in an oven for thermal polymerization.
[0051] (3) The sealed samples are placed in an oven, which needs to be sealed and evacuated. The oven heating program is set as follows: first, keep the temperature at 50-55°C for 12-24 hours; then heat to 70-75°C at a rate of 5-8°C / h and keep it for 8-16 hours; then heat to 100-110°C at a rate of 5-8°C / h and keep it for 8-16 hours; then cool to 70-75°C at a rate of 3-5°C / h and keep it for 12-24 hours; then cool to 45-50°C at a rate of 3-5°C / h and keep it for 12-24 hours, and then cool to room temperature; then place it in an oven and heat to 60°C for stress relief annealing for 48 hours, and then slowly cool to room temperature.
[0052] (4) The sample after stress relief annealing treatment is taken out, cut, and polished. The obtained organosilane composite plastic scintillator is very transparent and elastic. In the spectral test, it can be observed that the characteristic emission wavelength of the scintillator is 435nm, which can match the wavelength acceptance range of the photomultiplier tube and is near the peak value; the neutron / gamma discrimination test is carried out with a plutonium-beryllium neutron radiation source, and the pulse shape discrimination quality factor FoM=1.59±0.03 is obtained; the commercial EJ200 is used as a standard sample for comparison, and the 137 The relative light yield of the Cs gamma source was tested, and its relative light yield was 101% relative to that of EJ200; the prepared scintillator had no bubbles inside, no cracks outside, and high transparency.
[0053] Example 2
[0054] (1) The mass ratio of VT to DDS in the matrix was set to 75:25. 2.8 g VT and 0.7 g DDS were weighed according to the mass percentage, added into a test tube and ultrasonically mixed evenly. Then 0.07 g divinylbenzene (DVB) was added thereto and mixed evenly to prepare a mixed solution A. Then, according to the mass percentage, 1.05 g of the primary fluorescent dye 2,5-diphenyloxazole (PPO), 0.007 g of the secondary fluorescent dye 7-diethylamino-4-methylcoumarin (MDAC), and 0.00175 g of the initiator azobisisobutyronitrile (AIBN) were added to another test tube to obtain a mixed powder B; the mixed solution A was transferred to the test tube of the mixed powder B through a disposable dropper, mixed and shaken, and then ultrasonicated for 5 minutes. The next step can be performed after all the powder particles are completely dissolved, and a precursor solution C is obtained; at this time, the proportion of DVB in the precursor solution C is 2wt%, of which the proportion of PPO is 30wt%, the proportion of MDAC is 0.2wt%, and the proportion of AIBN is 0.05wt%.
[0055] (2) Purifying the precursor solution C by evacuating the solution and then filling it with an inert gas (nitrogen). The solution is evacuated for 3 minutes through a double-row pipe device, and then nitrogen is introduced for 2 minutes. The purification process is repeated 3 times. The test tube is sealed with a flamethrower and then placed in an oven for thermal polymerization.
[0056] (3) The sealed samples are placed in an oven, which needs to be sealed and evacuated. The oven heating program is set as follows: first, keep the temperature at 50-55°C for 12-24 hours; then heat to 70-75°C at a rate of 5-8°C / h and keep it for 8-16 hours; then heat to 100-110°C at a rate of 5-8°C / h and keep it for 8-16 hours; then cool to 70-75°C at a rate of 3-5°C / h and keep it for 12-24 hours; then cool to 45-50°C at a rate of 3-5°C / h and keep it for 12-24 hours, and then cool to room temperature; then place it in an oven and heat to 60°C for stress relief annealing for 48 hours, and then slowly cool to room temperature.
[0057] (4) The sample after stress relief annealing treatment is taken out, cut, and polished. The obtained organosilane composite plastic scintillator is very transparent and elastic. In the spectral test, it can be observed that the characteristic emission wavelength of the scintillator is 435nm, which can match the wavelength acceptance range of the photomultiplier tube and is near the peak value; the neutron / gamma discrimination test is carried out with a plutonium-beryllium neutron radiation source, and the pulse shape discrimination quality factor FoM=1.67±0.01 is obtained; the commercial EJ200 is used as a standard sample for comparison, and the 137 The relative light yield of the Cs gamma source was tested, and its relative light yield was 94% relative to that of EJ200; the prepared scintillator had no bubbles inside, no cracks outside, and high transparency.
[0058] Example 3
[0059] (1) The mass ratio of VT to DDS in the matrix was set to 70:30. 2.8 g of VT and 0.7 g of DDS were weighed according to the mass percentage, added into a test tube and ultrasonically mixed evenly. Then, 0.07 g of divinylbenzene (DVB) was added thereto and mixed evenly to prepare a mixed solution A. Then, according to the mass percentage, 1.05 g of the primary fluorescent dye 2,5-diphenyloxazole (PPO), 0.007 g of the secondary fluorescent dye 7-diethylamino-4-methylcoumarin (MDAC), and 0.00175 g of the initiator azobisisobutyronitrile (AIBN) were added to another test tube to obtain a mixed powder B; the mixed solution A was transferred to the test tube of the mixed powder B through a disposable dropper, mixed and shaken, and then ultrasonicated for 5 minutes. The next step can be performed after all the powder particles are completely dissolved, and a precursor solution C is obtained; at this time, the proportion of DVB in the precursor solution C is 2wt%, of which the proportion of PPO is 30wt%, the proportion of MDAC is 0.2wt%, and the proportion of AIBN is 0.05wt%.
[0060] (2) Purifying the precursor solution C by evacuating the solution and then filling it with an inert gas (nitrogen). The solution is evacuated for 3 minutes through a double-row pipe device, and then nitrogen is introduced for 2 minutes. The purification process is repeated 3 times. The test tube is sealed with a flamethrower and then placed in an oven for thermal polymerization.
[0061] (3) The sealed samples are placed in an oven, which needs to be sealed and evacuated. The oven heating program is set as follows: first, keep the temperature at 50-55°C for 12-24 hours; then heat to 70-75°C at a rate of 5-8°C / h and keep it for 8-16 hours; then heat to 100-110°C at a rate of 5-8°C / h and keep it for 8-16 hours; then cool to 70-75°C at a rate of 3-5°C / h and keep it for 12-24 hours; then cool to 45-50°C at a rate of 3-5°C / h and keep it for 12-24 hours, and then cool to room temperature; then place it in an oven and heat to 60°C for stress relief annealing for 48 hours, and then slowly cool to room temperature.
[0062] (4) The sample after stress relief annealing treatment is taken out, cut, and polished. The obtained organosilane composite plastic scintillator is very transparent and elastic. In the spectral test, it can be observed that the characteristic emission wavelength of the scintillator is 441nm, which can match the wavelength acceptance range of the photomultiplier tube and is near the peak value; the neutron / gamma discrimination test is carried out with a plutonium-beryllium neutron radiation source, and the pulse shape discrimination quality factor FoM=1.71±0.02 is obtained; the commercial EJ200 is used as a standard sample for comparison, and the 137The relative light yield of the Cs gamma source was tested, and its relative light yield was 92% relative to that of EJ200; the prepared scintillator had no bubbles inside, no cracks outside, and high transparency.
[0063] Example 4
[0064] (1) The mass ratio of VT to DDS in the matrix was set to 65:35. 2.8 g VT and 0.7 g DDS were weighed according to the mass percentage, added into a test tube and ultrasonically mixed evenly. Then 0.07 g divinylbenzene (DVB) was added thereto and mixed evenly to prepare a mixed solution A. Then, according to the mass percentage, 1.05 g of the primary fluorescent dye 2,5-diphenyloxazole (PPO), 0.007 g of the secondary fluorescent dye 7-diethylamino-4-methylcoumarin (MDAC), and 0.00175 g of the initiator azobisisobutyronitrile (AIBN) were added to another test tube to obtain a mixed powder B; the mixed solution A was transferred to the test tube of the mixed powder B through a disposable dropper, mixed and shaken, and then ultrasonicated for 5 minutes. The next step can be performed after all the powder particles are completely dissolved, and a precursor solution C is obtained; at this time, the proportion of DVB in the precursor solution C is 2wt%, of which the proportion of PPO is 30wt%, the proportion of MDAC is 0.2wt%, and the proportion of AIBN is 0.05wt%.
[0065] (2) Purifying the precursor solution C by evacuating the solution and then filling it with an inert gas (nitrogen). The solution is evacuated for 3 minutes through a double-row pipe device, and then nitrogen is introduced for 2 minutes. The purification process is repeated 3 times. The test tube is sealed with a flamethrower and then placed in an oven for thermal polymerization.
[0066] (3) The sealed samples are placed in an oven, which needs to be sealed and evacuated. The oven heating program is set as follows: first, keep the temperature at 50-55°C for 12-24 hours; then heat to 70-75°C at a rate of 5-8°C / h and keep it for 8-16 hours; then heat to 100-110°C at a rate of 5-8°C / h and keep it for 8-16 hours; then cool to 70-75°C at a rate of 3-5°C / h and keep it for 12-24 hours; then cool to 45-50°C at a rate of 3-5°C / h and keep it for 12-24 hours, and then cool to room temperature; then place it in an oven and heat to 60°C for stress relief annealing for 48 hours, and then slowly cool to room temperature.
[0067] (4) The sample after stress relief annealing treatment is taken out, cut, and polished. The obtained organosilane composite plastic scintillator is very transparent and elastic. In the spectral test, it can be observed that the characteristic emission wavelength of the scintillator is 438nm, which can match the wavelength acceptance range of the photomultiplier tube and is near the peak value; the neutron / gamma discrimination test is carried out with a plutonium-beryllium neutron radiation source, and the pulse shape discrimination quality factor FoM=1.70±0.03 is obtained; the commercial EJ200 is used as a standard sample for comparison, and the 137 The relative light yield of the Cs gamma source was tested, and its relative light yield was 88% relative to that of EJ200; the prepared scintillator had no bubbles inside, no cracks outside, and high transparency.
[0068] Example 5
[0069] (1) The mass ratio of VT to DDS in the matrix was set to 60:40. 2.8 g of VT and 0.7 g of DDS were weighed according to the mass percentage, added into a test tube and ultrasonically mixed evenly. Then, 0.07 g of divinylbenzene (DVB) was added thereto and mixed evenly to prepare a mixed solution A. Then, according to the mass percentage, 1.05 g of the primary fluorescent dye 2,5-diphenyloxazole (PPO), 0.007 g of the secondary fluorescent dye 7-diethylamino-4-methylcoumarin (MDAC), and 0.00175 g of the initiator azobisisobutyronitrile (AIBN) were added to another test tube to obtain a mixed powder B; the mixed solution A was transferred to the test tube of the mixed powder B through a disposable dropper, mixed and shaken, and then ultrasonicated for 5 minutes. The next step can be performed after all the powder particles are completely dissolved, and a precursor solution C is obtained; at this time, the proportion of DVB in the precursor solution C is 2wt%, of which the proportion of PPO is 30wt%, the proportion of MDAC is 0.2wt%, and the proportion of AIBN is 0.05wt%.
[0070] (2) Purifying the precursor solution C by evacuating the solution and then filling it with an inert gas (nitrogen). The solution is evacuated for 3 minutes through a double-row pipe device, and then nitrogen is introduced for 2 minutes. The purification process is repeated 3 times. The test tube is sealed with a flamethrower and then placed in an oven for thermal polymerization.
[0071] (3) The sealed samples are placed in an oven, which needs to be sealed and evacuated. The oven heating program is set as follows: first, keep the temperature at 50-55°C for 12-24 hours; then heat to 70-75°C at a rate of 5-8°C / h and keep it for 8-16 hours; then heat to 100-110°C at a rate of 5-8°C / h and keep it for 8-16 hours; then cool to 70-75°C at a rate of 3-5°C / h and keep it for 12-24 hours; then cool to 45-50°C at a rate of 3-5°C / h and keep it for 12-24 hours, and then cool to room temperature; then place it in an oven and heat to 60°C for stress relief annealing for 48 hours, and then slowly cool to room temperature.
[0072] (4) The sample after stress relief annealing treatment is taken out, cut, and polished. The obtained organosilane composite plastic scintillator is very transparent and elastic. In the spectral test, it can be observed that the characteristic emission wavelength of the scintillator is 438nm, which can match the wavelength acceptance range of the photomultiplier tube and is near the peak value; the neutron / gamma discrimination test is carried out with a plutonium-beryllium neutron radiation source, and the pulse shape discrimination quality factor FoM=1.73±0.01 is obtained; the commercial EJ200 is used as a standard sample for comparison, and the 137 The relative light yield of the Cs gamma source was tested, and its relative light yield was 76% relative to that of EJ200; the prepared scintillator had no bubbles inside, no cracks outside, and high transparency.
[0073] The following are sample photos, pulse shape discrimination performance analysis, excitation fluorescence spectrum analysis, thermogravimetric (TG) curve analysis and hardness analysis of the organosilane composite plastic scintillator obtained in Examples 1-5.
[0074] 1. Sample pictures
[0075] The successfully prepared organosilane composite plastic scintillator was cut, ground, polished and other mechanical processes. The photo under the fluorescent light is as follows: Figure 1 (a) shows the scintillator as a whole. There is no precipitation inside and the surface is smooth. The photo taken under 365nm ultraviolet light is shown in Figure 1 As shown in (b), the whole emits blue-purple fluorescence.
[0076] 2. Pulse shape discrimination performance and light yield analysis
[0077] Figure 2 is the pulse shape discrimination diagram of Examples 1-5 and the standard EJ276 scintillator; the entire pulse shape discrimination spectrum is based on 238Pu-Be source is a neutron radiation source. All events obtained in the channel number range of 0-350000 (equivalent to the electron energy equivalent range of 0-7000keVee) are integrated to obtain a two-dimensional PSD graph, and then the energy range of 200-1200keVee is selected to calculate the FoM value. Figure 1 shown. Figure 3 is 137 The pulse height spectrum under Cs gamma source irradiation uses the channel address of the abscissa corresponding to the highest point of the Compton edge to calculate the relative light yield compared with the standard sample EJ200.
[0078] In the organosilane composite plastic scintillator, such as Examples 1-5, we can see that in the organosilane composite plastic scintillator, with the increase of the mass fraction of DDS, the overall FoM value of the scintillator shows an increasing trend, and reaches a peak value when the DDS addition amount is 30wt%. The FoM value will not continue to increase when the DDS concentration is subsequently increased. This is because the added organic dye is limited, and the resulting TTA and transfer efficiency are limited. At the same time, we can calculate that the FoM value of commercial EJ276 is 1.33, and the FoM value of the organosilane composite plastic scintillator prepared by adding DDS is generally much higher than that of EJ276. Based on this, we can know that the neutron / gamma discrimination ability of the scintillator can be effectively improved by adding DDS. In the calculation of light yield, we can calculate the specific relative efficiency of light yield. As shown in the data of Examples 1-5, the relative light yield will decrease slightly with a small increase in DSS. When the added content exceeds 30wt%, the light yield will be greatly lost. This is because the added DDS contains a large amount of Si-O-Si bonds, which will cause light quenching and reduce the light yield of the scintillator. The light yield of Examples 1-5 is between 76% and 101% of EJ-200, and the PSD performance and light yield performance are comparable to or even better than commercial samples.
[0079] 3. Excitation-emission fluorescence spectrum
[0080] Figure 4It is the excitation-emission fluorescence spectrum of Example 3. We have selected the sample with the best PSD performance to analyze the excitation-emission spectrum. In the figure, we can observe two excitation peaks at 252nm and 275nm, which correspond to the fluorescence absorption of two matrices, DDS and VT. At 441nm, we can observe a characteristic blue emission peak, which is the fluorescence emission transferred from the primary fluorescent dye PPO to the secondary fluorescent dye MDAC, and there are no other characteristic emission peaks, indicating that the energy transfer efficiency is very high during the fluorescence energy resonance transfer process, indicating that the internal energy transfer efficiency of this composite scintillator is high and can effectively reduce energy loss. Compared with conventional scintillators, the emission wavelength of the organosilane composite plastic scintillator will produce a certain red shift, because the added DDS contains a large amount of silicon-oxygen bonds, which will cause red shift to a certain extent, but it has no effect, and the emission wavelength is still within the acceptance peak range of the photomultiplier tube.
[0081] 4. UV-Visible transmittance spectrum analysis
[0082] The quality of UV-visible light transmission performance corresponds to the self-absorption performance and self-luminous efficiency of the scintillator. Figure 5 As shown, we use a UV-visible spectrophotometer to test the UV-visible transmission spectrum of the scintillator at 250-800nm. Because the overall transparency of the scintillator is very high, at 450nm-800nm, the transparency of the scintillator will increase with the increase of DDS. When DDS is added to 30wt%, the transparency is already the best. Increasing the concentration of DDS will not increase the transmittance, but will only fluctuate within this range. It may even show a downward trend. This is because the added DDS has very good solubility for organic dyes, which can reduce the fluorescence quenching caused by the invisible aggregation of organic dyes in the scintillator, thereby effectively improving the transmittance. When the concentration of DDS is greater than 30wt%, because a large amount of Si-O-Si in the scintillator will cause severe light quenching, this quenching effect will gradually be greater than the promotion effect caused by increasing the solubility of the dye, so when the amount of DDS added is greater than 30wt%, the transmittance will even decrease. This proves that there is a mutual influence between the addition of DDS on the dissolution of organic dyes and the severe light quenching caused by a large amount of Si-O-Si, but overall it will effectively improve the optical performance of the scintillator.
[0083] 5. Thermogravimetric-thermogravimetric differential curve analysis
[0084] Under nitrogen atmosphere, we used thermogravimetric analysis to study the thermal stability of scintillators with different concentrations of DDS, and compared them with the pure PVT sample prepared in Example 6. Figure 6As shown. The temperature was increased from 30℃ to 800℃ at a heating rate of 10℃ / min. The solid mass of all samples containing DDS remained constant from the beginning until the weight loss began to be obvious at 120℃, while the pure PVT sample began to lose weight at 170℃. This is because the sample with the addition of DDS affects the cross-linked network structure of PVT, so the initial decomposition temperature will decrease. The first thermal degradation stage is at 150℃-250℃, which is mainly due to the thermal degradation and evaporation of some PVT short-chain oligomers, DDS short-chain polymers and fluorophores (PPO, MDAC), which accounts for a relatively small proportion. The second stage of degradation is at 250℃-350℃, which is relatively stable, because after the thermal degradation of low polymers and organic dyes, the remaining large chain segments with a high degree of crosslinking play a positive role in thermal stability. However, because the short-chain polymers of DDS will crack, compared with the pure PVT sample, in this temperature range, the weight loss curve of the DDS-added sample will be significantly lower than that of the pure PVT sample. Among the samples with added DDS, the best thermal stability is achieved when the amount of DDS added is 30wt%. This is because the bond energy of covalent bonds such as Si-O-Si is high and not easy to break, so the stability is good. However, as the content of DDS is further increased, the cross-linked network becomes loose, causing its thermal stability to decrease rapidly. The third thermal degradation stage is at 350℃-450℃. In this stage, the PVT cross-linked network is mainly disintegrated. The remaining cross-linked network structure further disintegrates at high temperature, and finally 2%-5% of solid residue remains. This is mainly the SiOC glass residue remaining after the thermal degradation of DDS. As for the pure PVT sample, it will be almost completely decomposed, and the remaining mass is about 0. In this section, we can see that the sample with 25wt% DDS added has the best thermal stability at this time. This is because as the temperature increases, the requirements for the cross-linked network are further increased, but as the DDS content increases, the tightness of the cross-linked network becomes worse, so the sample with the best thermal stability will shift towards the direction of less DDS concentration.
[0085] 6. Rebound performance analysis
[0086] The prepared organosilane composite plastic scintillator has excellent resilience, and the elasticity of the prepared scintillator increases with the increase of DDS concentration. It has strong resilience and can quickly recover to its original state after being squeezed by external force. Therefore, we selected the sample of Example 3 and conducted a detailed test on its elasticity. A blunt needle with a diameter of 0.79 mm was used to press the scintillator to test the resilience, the pressing depth was 1.5 mm, the continuous pressing time was 1 min, and then it was observed under a microscope. Figure 7As shown, it can be seen that from the beginning of observation, the surface of the scintillator has very deep depressions and marks. As time goes by, the depressions and marks will become shallower and shallower. After 30 seconds, most of the marks will disappear. At 4 minutes, the pressing marks almost completely disappear, and there is no damage as a whole. This is because the added DDS will weaken the cross-linking degree of PVT in the scintillator, making the elasticity of the scintillator stronger, which is inversely proportional to the hardness of the scintillator. Scintillators with 20wt%-40wt% DDS added have rebound performance, but their rebound time will be extended as the DDS decreases.
[0087] Example 6
[0088] The other conditions were the same as those in Example 1, except that the content of DDS in the matrix was changed, and the mass fraction of DDS was 0wt%. The FoM value was calculated to be 1.38, and the neutron / gamma discrimination capability was lower than that of the organosilane composite plastic scintillator containing DDS, and the UV-visible light transmittance was not much different.
[0089] Example 7
[0090] The other conditions were the same as those in Example 1, except that the content of DDS in the matrix was changed, and the mass fraction of DDS was 5wt%. The FoM value was calculated to be 1.45, and the neutron / gamma discrimination capability was improved, but the addition of DDS was small, and the FoM was still not significantly improved compared with the organic silane composite plastic scintillator with a large amount of DDS added, and the UV-visible light transmittance was not much different.
[0091] Example 8
[0092] The other conditions were the same as those in Example 1, except that the content of DDS in the matrix was changed to 10 wt %. The FoM value was calculated to be 1.51, the neutron / gamma discrimination capability was further improved, and the UV-visible light transmittance was not much different.
[0093] Example 9
[0094] The other conditions are the same as those in Example 3, except that the content of DDS in the matrix is changed, and the mass fraction of DDS is 15 wt %. The FoM value is calculated to be 1.56, and the neutron / gamma discrimination capability is further improved. It can be seen that there is a significant difference from the sample without adding DDS, and the UV-visible light transmittance is not much different.
[0095] Comparative Example 1
[0096] The other conditions were the same as those in Example 1, except that the content of DDS in the matrix was changed to 60 wt %. At this time, the prepared scintillator was already turbid, with low overall transparency, greatly reduced light yield, and greatly reduced performance.
[0097] Comparative Example 2
[0098] The other conditions are the same as those in Example 1, except that the scintillator is not purified and sealed in step (2), so that the polymerization reaction is carried out in the atmosphere. At this time, the surface of the prepared scintillator will have spot-like precipitation of varying sizes, and the whole will be slightly yellowish, and the overall PSD and light yield performance will be greatly reduced.
[0099] Comparative Example 3
[0100] The other conditions are the same as those in Example 1, except that the scintillator is not subjected to stress relief annealing in step (3), and is directly taken out for use after cooling. At this time, the prepared scintillator will, over time, precipitate a layer of white film on the surface, and cracks of varying sizes will appear on the surface, the light transmittance will drop significantly, and the performance of PSD and light yield will also drop rapidly, and it will soon be unable to be used normally.
Claims
1. An organosilane composite plastic scintillator with excellent neutron / gamma discrimination capability and a preparation method thereof, characterized in that: The organosilane composite plastic scintillator is composed of organosilane, organic plastic polymer, primary fluorescent dye and secondary fluorescent dye. The organosilane is diphenyldimethoxysilane (DDS), the organic polymer plastic is vinyltoluene (VT), the primary fluorescent dye is 2,5-diphenyloxazole (PPO), and the secondary fluorescent dye is 7-diethylamino-4-methylcoumarin (MDAC).
2. The organosilane composite plastic scintillator with excellent neutron / gamma discrimination capability and the preparation method thereof according to claim 1, characterized in that: The mass fraction of the organosilane DDS as a matrix in the composite scintillator is 20wt% to 40wt%.
3. The organosilane composite plastic scintillator with excellent neutron / gamma discrimination capability and the preparation method thereof according to claim 1, characterized in that: The mass fraction of the organic high molecular plastic VT as a matrix in the composite scintillator is 60wt% to 80wt%.
4. The organosilane composite plastic scintillator with excellent neutron / gamma discrimination capability and the preparation method thereof according to claim 1, characterized in that: The mass fraction of the main fluorescent dye PPO in the organic silane composite plastic scintillator is 30wt%.
5. The organosilane composite plastic scintillator with excellent neutron / gamma discrimination capability and the preparation method thereof according to claim 1, characterized in that: The mass fraction of the secondary fluorescent dye MDAC in the organosilane composite plastic scintillator is 0.2 wt %.
6. An organosilane composite plastic scintillator with excellent neutron / gamma discrimination capability and a preparation method thereof according to any one of claims 1 to 5, characterized in that: The method comprises the following steps: preparing DDS, VT and divinylbenzene (DVB), stirring and ultrasonicating them to make them uniformly mixed, and obtaining a mixed solution A; preparing PPO, MDAC and azobisisobutylnitrile (AIBN) to obtain a mixed powder B; adding the mixed powder B to the mixed solution A, and then dissolving it through ultrasonic dispersion to obtain a mixed precursor solution C; pouring the mixed precursor solution C into a customized glass mold, and ultrasonically dispersing it again; and then purifying the precursor solution C, wherein the purification treatment is vacuuming and then filling it with an inert gas, and the purification treatment is repeated ≥3 times. Then, a thermal polymerization reaction is carried out in a vacuum environment, and after the reaction is completed, a stress relief annealing treatment is carried out, and finally an organic silane composite plastic scintillator is obtained.
7. The organosilane composite plastic scintillator with excellent neutron / gamma discrimination capability and the preparation method thereof according to claim 6, characterized in that: The mass ratio of DDS to VT is 20:80 to 40:
60. In the mixed precursor solution C, the mass fraction of PPO is 30wt%, the mass fraction of MDAC is 0.2wt%, the mass fraction of azobisisobutyronitrile (AIBN) is 0.05wt%, and the mass fraction of divinylbenzene (DVB) is 2wt%.
8. The organosilane composite plastic scintillator with excellent neutron / gamma discrimination capability and the preparation method thereof according to claim 6, characterized in that: The inert gas is nitrogen, and the repeated purification process is performed three times.
9. The organosilane composite plastic scintillator with excellent neutron / gamma discrimination capability and the preparation method thereof according to claim 6, characterized in that: The polymerization reaction process is as follows: first, keep the temperature at 50-55°C for 12-24h; then heat it to 70-75°C at a rate of 5-8°C / h and keep it for 8-16h; then heat it to 100-110°C at a rate of 5-8°C / h and keep it for 8-16h; then cool it to 70-75°C at a rate of 3-5°C / h and keep it for 12-24h; then cool it to 45-50°C at a rate of 3-5°C / h and keep it for 12-24h, cool it to room temperature after keeping it; then place it in an oven and heat it to 60°C for stress relief annealing for 48h, and then slowly cool it to room temperature.
10. The organosilane composite plastic scintillator with excellent neutron / gamma discrimination capability and the preparation method thereof according to claim 6, characterized in that: The organic silane composite plastic scintillator has a strong ability to distinguish neutrons and gamma rays and has good radiation resistance, and can be applied to neutron detection in a pulse radiation field mixed with neutrons and gamma rays.
Citation Information
Patent Citations
Polysiloxane-based plastic scintillator and preparation method and application thereof
CN113999529A
High-hardness polysiloxane scintillator as well as preparation method and application thereof
CN117965032A
Gel skeleton-plastic scintillator with neutron / gamma discrimination capability and preparation method thereof
CN118501926A